2021
DOI: 10.1002/minf.202100011
|View full text |Cite
|
Sign up to set email alerts
|

Locally Optimizable Joint Embedding Framework to Design Nitrogen‐rich Molecules that are Similar but Improved

Abstract: Deep learning has shown great potential for generating molecules with desired properties. But the cost and time required to obtain relevant property data have limited study to only a few classes of materials for which extensive data have already been collected. We develop a deep learning method that combines a generative model with a property prediction model to fuse small data of one class of molecules with larger data in another class. Common low‐level physicochemical properties are jointly embedded into a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…MAE is averaged over the three random train test splits, and the best model and featurization scheme that gives the minimum MAE is chosen. Autoencoder in the joint embedding framework is trained with 100 K molecules from MOSES 40 in addition to the entire set of 401 energetic molecules 35 . Finally, the best model and featurization scheme chosen from model cross validation process is used to predict the detonation velocity of each ferroelectric material in the dataset.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MAE is averaged over the three random train test splits, and the best model and featurization scheme that gives the minimum MAE is chosen. Autoencoder in the joint embedding framework is trained with 100 K molecules from MOSES 40 in addition to the entire set of 401 energetic molecules 35 . Finally, the best model and featurization scheme chosen from model cross validation process is used to predict the detonation velocity of each ferroelectric material in the dataset.…”
Section: Methodsmentioning
confidence: 99%
“…The eight models include Gaussian Process Regression, Kernel Ridge Regression, Support Vector Regression, Random Forest, Lasso Regression, k-Nearest Neighbors, Gradient Boosting and Ridge Regression. Previous studies on structure property prediction in energetic materials have shown good performance with these models 35,36 . Hyperparameter optimization is performed on each model (and for each featurization) using grid search with 5-fold cross validation.…”
Section: Machine Learningmentioning
confidence: 96%
See 1 more Smart Citation
“…Once they have been rigorously validated, computational forward design models allow us to not only quantify properties and performance but also to understand the underlying mechanics of the ignition and combustion process, such as the crucial hotspot physics and its connection to the microstructure [1,16]. In recent years sev-eral research groups have furthered understanding of the relationships among structure, property, and performance of a range of CHNO EMs [44][45][46][47]. These studies have revealed important relationships among porosity [1], pore size [1,48], shape and distribution [15,45,[49][50][51], and other morphological features such as asperities and interfaces between crystals and binders [46,52], and their effects on the sensitivity of the composite material.…”
Section: Forward and Inverse Designmentioning
confidence: 99%
“…In the field of energetic materials, the availability of a complete public dataset is still the bottleneck for building ML models. In most studies, researchers chose to gather data from literature [12][13][14] and extracted them from public databases [15][16][17], while a few others used results from theoretical calculations [18,19]. In this study, we extracted data from the literature.…”
Section: Data Collectionmentioning
confidence: 99%